Cultural Encounters in the BIPA Classroom: A Cross-Cultural Understanding of International students’ Perceptions of Indonesian Culture - Tiawati, Refa Lina; Tatalia, Ricci Gemarni; Dwintia, Suci; Rahmad, Hari Adi; Nawi, Nuradlin Syafini; Kurnia, Maya Dewi (Jurnal Gramatika, 2025)
This study explores how international students perceive Indonesian culture while participating in the Bahasa Indonesia for Foreign Speakers (BIPA) program at Padang State University. Framed within Cross-Cultural Understanding (CCU), the study investigates how students’ cultural backgrounds, prior experiences, and exposure to cultural content in language teaching shape their engagement and motivation. Using a descriptive qualitative case study approach, data were collected through in-depth interviews, classroom observations, and documentation. The findings show that most students positively perceive Indonesian culture, particularly appreciating traditions, hospitality, and food. However, challenges arise with abstract cultural values, such as indirect communication, hierarchical relationships, and concepts of politeness, which sometimes contrast with students' native cultural norms. Students from Southeast Asian countries reported smoother cultural adjustment than those from Western countries. Furthermore, students favored experiential learning—such as field trips, cooking classes, and cultural performances—over theoretical cultural instruction. These insights reinforce the importance of integrating cultural content into language instruction but also highlight the need for culturally responsive pedagogy that considers learners’ diverse cultural frameworks. The study suggests incorporating CCU models (e.g., Byram's ICC Bennett's DMIS) to support intercultural reflection, identity development, and deeper engagement. Future research should explore the longitudinal impacts of cultural learning and implement structured tools to evaluate intercultural competence development.